Media policy and its impact on the level of objectivity in the Iraqi media : A study from the communicators’ point of view in the Iraqi medi outlets for the period from (1/5/2021 to 1/9/2021) - Al-Hasani, Majeed Abboud Fahad (ALBAHITH ALALAMI, 2023)
The research aims to reveal the impact of media policy in Iraqi media outlets on the level of objectivity in these outlets. A study from the communicators’ point of view where the researcher used a survey method on the communicators in media outlets to reveal the extent of media policies knowledge as well as the pressures exerted by this policy on communicators in media outlets. It also reveals the extent of their commitment to objectivity, neutrality in dealing with information and the way used to transfer it. The research sample included (179) respondents from communicators in a range of Media outlets such as (Press, Radio, and Television), The researcher was careful with the diversity of the sample, and the targeted media outlets. The research found that the majority of respondents have knowledge of the media outlets’ policies and agree with them. It put pressure on them in terms of objectivity, since most of them were warned as a result of covering topics neutrally and objectively. Results also indicate that they alternatively use social media as a broader range of freedoms.